Contributory Factors Of Antimicrobial Resistance Among Females Presenting With Culture-Positive Urinary Tract Infection In A Tertiary Care Hospital - Ali, Laraib; Shahid, Afshan; Faisal, Farhan; Usama, Syed Mohammad; Nasir, Mehreen; Kayani, Rafia Masud (Journal of Rawalpindi Medical College, 2026)
Objective: This study aims to identify the frequency and associated factors of multidrug resistance causing UTI in females presenting in the Urology department of Shifa International Hospital, Islamabad. Methods: This cross-sectional Study was done from July to December 2024 at the Urology department of Shifa International Hospital, Islamabad, using a sample of 317 cases. Samples were included with non-probability consecutive sampling. A structured questionnaire was used to collect the data, including administrative details, sociodemographic information, clinical status, and urine culture reports. Data were entered and analyzed by the Statistical Package for Social Sciences SPSS version 24. Bivariate analysis was done for demographic variables and resistance patterns. Results: Out of 317 cases of culture-positive urinary tract infection, the mean age of the respondents was 55.85 years. Regarding the microbe, the most common organism was Escherichia coli 225 (70.98%), followed by Klebsiella pneumoniae 43 (13.56%). Multidrug resistance was seen in 218 (68.7%) of the cases. Significant associations were found between marital status, comorbid conditions, presence of blood in urine, antibiotic use history, and the type of infecting microbe. Conclusion: Antimicrobial resistance was seen in 218 (68.7%) of the females with culture-positive urinary tract infections. Regarding the microbe, the most common organism was Escherichia coli 225 (70.98%). Significant associated factors with multidrug resistance included marital status, diabetes, hypertension, frequent antibiotic use, and the presence of blood in urine and gram-negative organisms. To prevent the emergence of resistance and encourage responsible consumption of antibiotics, the results highlight the critical need for enhanced antibiotic stewardship initiatives. Keywords: Drug Resistance, Microbial, Urinary Tract Infections, Females